A comprehensive overview of NFTs (Trinity Journal of Management, IT & Media (TJMITM), 2022)
In recent years, the Non-Fungible Token (NFT) has attracted a great audience towards them. As the research on NFTs is growing immensely, it is essential to value the existing research on NFTs and Blockchains, to identify potential future research areas. This paper brings forth the case study review, blockchain, NFTs monetary decentralization, and non-fungible & fungible Assets. The objective of this paper was to predict the future market of NFTs through different case study learnings. The results extracted from the market reviews and case studies demonstrate two main classifications: the first would be the NFTs growing remarkably through time and becoming the key value asset with a well-developing ecosystem.
Keywords: Blockchain; Fungible & Non-Fungible; Market analysis